A Stochastic Programming Method for Resources Allocation in Education of Higher Vocational College. (September 2020) - Kong, Xiangming; Wang, Donglin; Wang, Yu; Wang, Nan
Abstract: A stochastic education resources management (SERM) model has been proposed to solve resource-allocation problems in education under uncertainty. The advantages of SERM are as follows: (1) it is capable for dealing with uncertainty which may exhibit random feature in the right-side of constraints; (2) the optimal education resource-allocation strategies for each higher vocational college under different constraint levels can be generated. The application in education resources sharing systems indicates that the optimal resource-allocation strategies generated by the SERM model can increase the total output of education value, which includes the personnel, technological and social outputs.